You are Here: Home >< Maths

# C3 - Functions question watch

Announcements
1. Hi,

I'm a bit stuck on this question and would really appreciate it if someone could help:

The function f is defined by f:x=(2x+5)/3

(the inverse function) f^(-¹)=(3x-5)/2

Show that f(-¹)(3) (the inverse function of 3) is the solution of the equation
f(x)=3

Thanks!
2. The function f is defined by f:x=(2x+5)/3

(the inverse function) f^(-¹)=(3x-5)/2

Show that f(-¹)(3) (the inverse function of 3) is the solution of the equation
f(x)=3

well first....

.....sub in x=3 into f^(-¹)=(3x-5)/2 so you get f^(-¹)(3) = 2

.....and now just work out (2x+5)/3 = 3 is and show that it equals 2.

so (2x+5) = 9

2x = 9-5
2x = 4
x=2 and it works!!

TSR Support Team

We have a brilliant team of more than 60 Support Team members looking after discussions on The Student Room, helping to make it a fun, safe and useful place to hang out.

This forum is supported by:
Updated: February 28, 2006
Today on TSR

### The Simpsons...

How would you end the show?

### University open days

• University of Lincoln
Wed, 12 Dec '18
• Bournemouth University
Midwifery Open Day at Portsmouth Campus Undergraduate
Wed, 12 Dec '18
• Buckinghamshire New University
Wed, 12 Dec '18
Poll
Useful resources

### Maths Forum posting guidelines

Not sure where to post? Read the updated guidelines here

### How to use LaTex

Writing equations the easy way

### Study habits of A* students

Top tips from students who have already aced their exams